Enhanced Red Emission from Europium Doped Yttrium Oxide Nano Phosphor - Singh, Devender; Singh Kadyan, Pratap; Tanwar, Vijeta; Nishal, Vandna; Han, Sang-Do; Singh, Ishwar (Asian Journal of Chemistry, 2012)
Facile combustion method has been utilized for the synthesis of europium-doped yttrium oxide red nano phosphor with the inclusion of alkali metal. The red nano phosphor having the general formula (Y1-xEux)2-yNayO3-y, where 0.004 £ x £ 0.2 and Na+ is in the mole ratio 0.025 to 0.2 mol has been reported. Luminescence intensity of nano phosphor greatly enhanced with the inclusion of Na+ ions along with the doping of europium. The materials are soft with fine crystal size less than the 30 nm. X-ray diffraction spectrum and scanning electron micrograph of the materials are also taken for further studying the morphology of the luminescent compound.